Validation of a brief image elicitation task as an indicator of subjective wellbeing in the general population - J. David Pincus (Frontiers Media S.A., 2024)
BackgroundA novel image-based method (AgileBrain) demonstrates construct validity as a measure of wellbeing in the general working adult population.MethodAnalysis of data from four large nationally representative samples of American full-time workers employed by mid-to-large size companies conducted in November 2021 (n = 812), May 2022 (n = 810), June 2023 (n = 986), and January 2024 (n = 1,179).ResultsAcross all four studies, AgileBrain demonstrates convergent validity across multiple established indicators of subjective wellbeing including the Patient Health Questionnaire (PHQ-9), Center for Epidemiological Studies Depression Scale (CESD-10), Generalized Anxiety Disorder Scale (GAD-7), Neuroticism (BFI-S), UCLA Loneliness Scale, Perceived Stress Scale (PSS-10), Coping Styles (Brief COPE-28), self-reported diagnosed neurodiversity conditions and symptoms, and trauma history.ConclusionResults across these studies suggest that AgileBrain is useful as a screening tool for detecting compromised wellbeing in terms of construct validity. Given strong preferences for brief, gamified assessments, the validity advantages stemming from less consciously controllable responses, and the statistical advantages of measures associated with high response rates and normal distributions, AgileBrain emerges as strong tool for assessing subjective wellbeing at the population level and offers a promising approach to monitoring treatment effectiveness.